Optimization of Law Enforcement by Gakkum Unit through the Electronic Traffic Law Enforcement System to Reduce Traffic Violations in the Jurisdiction of the Pemalang Police Resort - Made Intan Isaka Sri Maharani Intan (Tanggon Kosala, 2023)
Enforcement of traffic violations through the Electronic Traffic Law Enforcement system is one form of effort to reduce traffic violations. Regarding this matter, this research aims to optimize law enforcement of traffic by the Gakkum Unit of the Traffic Unit of the Pemalang Police Resort through the ETLE system, especially the Mobile Hand Held type, towards traffic violations in the jurisdiction of the Pemalang Police Resort. Additionally, the Mobile Hand Held ETLE system is based on the ANPR (Automatic Number Plate Recognition) method. This research uses a qualitative approach and field research type. Conceptually, the analysis tool used in this research is the use of management theory, law enforcement theory, and SWOT theory. The concepts used are optimization concept and ETLE concept. The results show that the ETLE system has an influence on the dynamics of the number of traffic violations in the jurisdiction of the Pemalang Police Resort, as shown in the data of traffic violations in 2020 (before the implementation of the ETLE system in the jurisdiction of the Pemalang Police Resort) and in 2021 (the first year of the implementation of the ETLE system), which decreased by 5,916. Despite this, there are several obstacles faced in using the ETLE system, such as budget limitations, infrastructure, technical issues, and societal patterns. Based on the results of this research, it is recommended that the Gakkum Unit of the Traffic Unit of the Pemalang Police Resort can optimize the ETLE system as an effort to enforce traffic violations and develop more accurate ANPR methods.